Flower bud differentiation in apricot - Németh, Sz.; Szalay, L.; Reményi, M. L. (International Journal of Horticultural Science, 2008)
The flower bud development is an especially complex process from initiation to blooming. Our main objective was to analyze paradormancy; the first stage of this process in our collection of varieties in the vicinity of Budapest, in Hungary. We have analyzed three varieties with different winter hardiness. `Ceglédi bíborkajszi’ is one of the most frost susceptible in our collection of varieties, when the flower bud differentiation started in early August, and all flower organ initials evolved in beginning of September. The flower bud differentiation of the most winter hardy variety, `Rózsakajszi C.1406’ started in the end of August, and all flower organs were noticed at middle of September. `Gönci magyar kajszi’ is a medium frost hardiness apricot variety, its phenological process composes transition between two mentioned above varieties.